Personality Perception of Robot Avatar Teleoperators in Solo and Dyadic Tasks - Bremner, Paul Adam; Celiktutan, Oya; Gunes, Hatice (Frontiers in Robotics and AI, 2017)
Humanoid robot avatars are a potential new tele-communication tool whereby a user is remotely represented by a robot that replicates their arm and head movements. They have been shown to have a number of benefits over more traditional media such as phones or video calls. However using a tele-operated humanoid as a communication medium inherently changes the appearance of the operator, and appearance based stereotypes are used in interpersonal judgements (whether consciously or unconsciously). One such judgement that plays a key role in how people interact is personality. Hence, we have been motivated to investigate if and how using a robot avatar alters the perceived personality of tele-operators. To do so we carried out two studies where participants performed 3 communication tasks, solo in study one and dyadic in study 2, and were recorded on video both with and without robot mediation. Judges recruited using online crowdsourcing services then made personality judgements of those in the video clips. We observed that judges were able to make internally consistent trait judgements in both communication conditions. However, judge agreement was affected by robot mediation, although which traits were affected was highly task dependent. Our most important finding was that in dyadic tasks personality trait perception was shifted to incorporate cues relating to the robot's appearance when it was used to communicate. Our findings have important implications for tele-presence robot design and personality expression in autonomous robots.